Turkish and Refugee Students’ Views about Their National Belonging (Journal of Education and Educational Development, 2022)
The purpose of this study is to determine Turkish and refugee middle school students views on their national belonging. The study employed the qualitative research approach, and, aligned with the purpose, semi-structured interviews were conducted with Turkish and refugee students. Data were analyzed using the content analysis method. Results showed that the most important common features for national belonging of both Turkish and refugee students were the common language they spoke and the place they lived in and the difference of views regarding national belonging were in terms of discrimination. Regarding Turkish society expectations of them, both groups emphasized universal values such as being hardworking and being a good person, but their perceptions of serving the state differed. As for what Turkish and refugee students should do for this society, Turkish students believed that they should be hardworking and refugee students thought that they should be good people. It can be said that the differences of opinion between Turkish students and refugee students who migrated to Turkey would decrease if both groups came together on the subject of universal values.